Comparing adverse effects, short term outcomes, and cost implications of hyperthermic intravesical chemotherapy with Mitomycin-C and intravesical bacillus Calmette–Guerin instillation (Moscow-I strain) in the management of intermediate and high-risk nonmuscle invasive bladder cancer - Yuvaraja B Thyavihally; Santosh S Waigankar; Preetham Dev; Ashish Asari; Abhinav P Pednekar; Nevitha Athikari; Abhijit Raut; Archan Khandekar; Naresh Badlani (Urology Annals, 2021)
Introduction: The recommended treatment for intermediate and high-risk nonmuscle invasive bladder cancer (NMIBC) is adjuvant intravesical bacillus Calmette–Guerin (BCG) instillation. However, up to 50% experience tumor recurrences even after adjuvant BCG, and many patients develop local or systemic adverse effects. Our study compared adverse effects, short-term recurrence rates, and cost-implications of BCG therapy to Hyperthermic Intra-VEsical Chemotherapy (HIVEC) with Mitomycin-C (MMC) in these patients. Materials and Methods: Retrospective analysis of intermediate and high-risk NMIBC patients who received either intravesical BCG or HIVEC® after transurethral resection of bladder tumor in our institute (January 2017 to March 2020) was done. Twenty-two patients who received HIVEC and 29 who received BCG were analyzed. We used SPSS Statistics v20.0 (IBM Corp., Armonk, NY, USA) software for the statistical analysis. Results: Nineteen (86.4%) patients in the HIVEC group had no adverse effects. Two (9.1%) patients had Grade I lower urinary tract symptoms (LUTS) treated symptomatically. One patient developed UTI after HIVEC, and further cycles were stopped (Grade II). BCG group had a higher rate of Grade III adverse effects in six (20.7%) patients. Median follow-up was 10.5 and 22 months. The tumor recurred in one (4.5%) and six (20.7%) patients in HIVEC and BCG groups, respectively. There was no difference in recurrence-free survival at 18 months and the cost for the HIVEC therapy was more. Conclusions: HIVEC with MMC is a reasonable adjuvant treatment option in NMIBC, which is well tolerated, albeit increased cost of the treatment. Randomized trials with more follow-up are required for further conclusion.